Interleukin-1 receptor 1 knockout has no effect on amyloid deposition in Tg2576 mice and does not alter efficacy following Aβ immunotherapy - Das, Pritam (BioMed Central, 2006)
BACKGROUND: Microglial activation has been proposed to facilitate clearance of amyloid β protein (Aβ) from the brain following Aβ immunotherapy in amyloid precursor protein (APP) transgenic mice. Interleukin-1 receptor 1 knockout (IL-1 R1-/-) mice are reported to exhibit blunted inflammatory responses to injury. To further define the role of IL-1-mediated inflammatory responses and microglial activation in this paradigm, we examined the efficacy of passive Aβ immunotherapy in Tg2576 mice crossed into the IL-1 R1-/- background. In addition, we examined if loss of IL-1 R1-/- modifies Aβ deposition in the absence of additional manipulations. METHODS: We passively immunized Tg2576 mice crossed into the IL-1 R1-/- background (APP/IL-1 R1-/- mice) with an anti-Aβ1-16 mAb (mAb9, IgG2a) that we previously showed could attenuate Aβ deposition in Tg2576 mice. We also examined whether the IL-1 R1 knockout background modifies Aβ deposition in untreated mice. Biochemical and immunohistochemical Aβ loads and microglial activation was assessed. RESULTS: Passive immunization with anti-Aβ mAb was effective in reducing plaque load in APP/IL-1 R1-/- mice when the immunization was started prior to significant plaque deposition. Similar to previous studies, immunization was not effective in older APP/IL-1 R1-/- mice or IL-1 R1 sufficient wild type Tg2576 mice. Our analysis of Aβ deposition in the untreated APP/IL-1 R1-/- mice did not show differences on biochemical Aβ loads during normal aging of these mice compared to IL-1 R1 sufficient wild type Tg2576 mice. CONCLUSION: We find no evidence that the lack of the IL-1 R1 receptor influences either Aβ deposition or the efficacy of passive immunotherapy. Such results are consistent with other studies in Tg2576 mice that suggest microglial activation may not be required for efficacy in passive immunization approaches.